The Concept of Waqf: Analysis of Waqf Thought According to Imam Shafi'i - Wahyuddin, Wahyuddin; Misbahuddin, Misbahuddin; Siradjuddin, Siradjuddin (Universitas Muhammadiyah Makassar, 2024)
This research describes the thoughts of Imam Syafi'i on waqf, one of the important concepts in Islam that involves the transfer of property ownership for perpetual charitable purposes. Waqf it self means the release of wealth intended to build facilities and infrastructure needed by To promote community well-being human life. Imam Syafi'i is one of the great scholars who views waqf as a powerful instrument in promoting social welfare and providing sustainable benefits for the Muslim community. He believes that waqf is the surrender of a property or wealth to Allah for charitable use and cannot be revoked by the waqif (the one making the waqf), meaning that waqf with a specific time limit is not permissible because the waqif, who has dedicated their property to Allah, cannot reclaim the waqf property. The research method used in this study is a descriptive qualitative study with a field survey approach. The results of this investigation suggest that the land was dedicated as a waqf. is no longer the individual's (waqif's) ownership but has transformed into the ownership of the community (belonging to Allah). As a result, the dedicated property cannot be traded, donated, or inherited because it is no longer personal property but public ownership (belonging to the community).